Perception of Financial and Non-financial Indicators of Value Creation in Their Reception and Provision with a Focus on Suppliers - Dana KUSNIROVA; Maria DURISOVA (Communications of International Proceedings, 2021)
Today, an enterprise has to face several obstacles in order to prosper, grow and secure its existence in the market. These barriers affect its market position, competitiveness, performance, and profitability. Therefore, the enterprise is trying to find a way to acquire stakeholders and thus ensure long-term and sustainable relationships. If an enterprise pays attention to its business partners, if it tries to perceive and fulfil their needs, requirements, and perceptions of their opinions or attitudes, it creates value for them. It is value creation for stakeholders that is an essential step in creating good mutual relations with its business partners. The paper's content is to bring a closer look at the issue of value creation indicators with a focus on the suppliers as the major enterprise's stakeholder. The paper describes the provision and reception of financial and non-financial indicators of value creation in 149 companies (108 from Slovakia and 41 from other countries), perception of the same value in providing and receiving it. The fundamental outcomes resulting from the fulfilment of the goal are that enterprises in Slovakia and other countries still consider financial indicators more important than non-financial ones. They attribute greater dynamism to financial indicators in providing values than in receiving them.
Keywords: Indicators; Financial Value; Non-Financial Value; Perception.